2014
DOI: 10.1063/1.4897974
|View full text |Cite
|
Sign up to set email alerts
|

Water transport through functionalized nanotubes with tunable hydrophobicity

Abstract: Molecular dynamics simulations are used to study the occupancy and flow of water through nanotubes comprised of hydrophobic and hydrophilic atoms, which are arranged on a honeycomb lattice to mimic functionalized carbon nanotubes (CNTs). We consider single-file motion of TIP3P water through narrow channels of (6,6) CNTs with varying fractions (f) of hydrophilic atoms. Various arrangements of hydrophilic atoms are used to create heterogeneous nanotubes with separate hydrophobic/hydrophilic domains along the tub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…The average number of confined water molecules increase exponentially with the charge percentage as seen in figure 2(b). This increase in average number of confined water molecules is in correspondence with earlier computational study 32 and suggests that the electrostatic interactions between the CNT and water play a dominant role compared to the vDW interactions 13 during the filling process.…”
Section: Variation In Confined Water Moleculessupporting
confidence: 89%
See 1 more Smart Citation
“…The average number of confined water molecules increase exponentially with the charge percentage as seen in figure 2(b). This increase in average number of confined water molecules is in correspondence with earlier computational study 32 and suggests that the electrostatic interactions between the CNT and water play a dominant role compared to the vDW interactions 13 during the filling process.…”
Section: Variation In Confined Water Moleculessupporting
confidence: 89%
“…There are several theoretical models 12,13 which describe the permeation of water through nanotube. Simulations have provided invaluable insights about the structure, dynamics and thermodynamics 14,15 of water confined inside pristine nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, we estimated the contact angle for the hydrophobic case to be around 96.5 • which indicates a slight hydrophobicity of the surface, similarly to the one computed by Hummer et al [21], Moskowitz et al, [71] and Kohler et al [48] considering the same interaction strength (ε = 0.2703 kJ/mol). In the superhydrophobic system, where ε sh co is 0.047 kJ/mol, we obtained a contact angle of ≈ 132 • , much larger than 90 • .…”
Section: Discussionmentioning
confidence: 77%
“…The value of ε CO established the amount of hydrophobicity of the carbon wall. In this work we have used a value of ε CO widely used for water in graphite confinement [21,48,71,72] correponding to a contact angle of around 96.5 • . For comparison, we have also used a superhydrophobic water-carbon interaction value previouly , filled with water molecules (red for oxygens and white for hydrogens).…”
Section: A Tuning the Hydrophobicity Of The Interaction Potentialmentioning
confidence: 99%
“…While graphene is a purely hydrophobic material, MoS 2 sheets have both hydrophobic (S) and hydrophilic (Mo) sites. Recent studies have shown that the water dynamics and structure inside hydrophobic or hydrophilic pores can be quite distinct regarding the pore size [28][29][30] and even near hydrophobic or hydrophilic protein sites. 31 Three cations are considered: the standard monovalent sodium (Na + ), the divalent zinc (Zn 2+ ), and the trivalent iron (Fe 3+ ).…”
Section: Introductionmentioning
confidence: 99%